2023
DOI: 10.3390/polym15153258
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Denture Base Materials: A Review

Ahmed Yaseen Alqutaibi,
Abdulmajeed Baik,
Sarah A. Almuzaini
et al.

Abstract: An ideal denture base must have good physical and mechanical properties, biocompatibility, and esthetic properties. Various polymeric materials have been used to construct denture bases. Polymethyl methacrylate (PMMA) is the most used biomaterial for dentures fabrication due to its favorable properties, which include ease of processing and pigmenting, sufficient mechanical properties, economy, and low toxicity. This article aimed to comprehensively review the current knowledge about denture base materials (DBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 156 publications
(347 reference statements)
0
20
0
Order By: Relevance
“…To transfer food temperature to the oral tissues, DBMs must possess sufficient thermal conductivity. If a material has low thermal conductivity, it will generate heat during denture production, thereby resulting in surface crazing [ 2 ]. Furthermore, low conductivity may compromise a patient’s capacity to perceive food temperature, meaning particularly hot beverages may burn the sensitive soft tissues in the throat or esophagus without the patient realizing it.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…To transfer food temperature to the oral tissues, DBMs must possess sufficient thermal conductivity. If a material has low thermal conductivity, it will generate heat during denture production, thereby resulting in surface crazing [ 2 ]. Furthermore, low conductivity may compromise a patient’s capacity to perceive food temperature, meaning particularly hot beverages may burn the sensitive soft tissues in the throat or esophagus without the patient realizing it.…”
Section: Reviewmentioning
confidence: 99%
“…The surface hardness of a material affects the material wear resistance and refers to the plastic deformation of specimens subjected to an indentation load [ 2 ]. Researchers in one study compared two types of PMMA DBMs which are Acralyn-H and DPI to two types of flexible dentures (Flexident and Valplast) and found that the hardness of the PMMA DBMs was higher than that of the flexible DBMs, with values of 82.5 ± 3.779 (VHN) for Acralyn-H, 76.9 ± 4.771 (VHN)for DPI, 67.4 ± 1.955 (VHN)for Flexident, and 66.0 ± 2.78 (VHN) for Valplast [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Rehabilitation of edentulous patients with conventional removable dentures is a standard treatment protocol [ 1 , 2 ], and polymethyl methacrylate (PMMA) remains the most commonly used material for the fabrication of denture bases [ 3 , 4 , 5 , 6 , 7 ]. In addition to the well-known analogue techniques for the fabrication of denture bases, contemporary digital technologies are also available today and are used in everyday dental practise.…”
Section: Introductionmentioning
confidence: 99%